Capacitive effects in IGBTs limiting their reliability under short circuit. (September 2017) - Reigosa, P.D.; Iannuzzo, F.; Rahimo, M.; Blaabjerg, F.
Abstract: The short-circuit oscillation mechanism in IGBTs is investigated in this paper by the aid of semiconductor device simulation tools. A 3.3-kV IGBT cell has been used for the simulations demonstrating that a single IGBT cell is able to oscillate together with the external circuit parasitic elements. The work presented here through both circuit and device analysis, confirms that the oscillations can be understood with focus on the device capacitive effects coming from the interaction between carrier concentration and the electric field. The paper also shows the 2-D effects during one oscillation cycle, revealing that the gate capacitance changes according with the shape of the electric field due to the charge distribution in the n-base. It has been identified that the time-varying capacitance leads to parametric oscillations together with the stray gate inductance, which limit the reliability of the IGBT. Highlights: The IGBT short-circuit robustness is compromised by an oscillation phenomenon occurring under adverse combinations of large stray inductances under low VCE, high VGE and low T. The weak electric field at the emitter is the key to trigger the oscillations. It is possible to relate the electric field distortions to gate capacitance variations, and associate the capacitance variation with charge-storage effects occurring at the surface of the IGBT. A parametric oscillation takes place during the IGBT short circuit, whose time-varying element is the Miller capacitance, leading to an amplification mechanism.